Beethoven - Mars, W.T. (artist):::Creator::::::::::::; Mirsky, Reba Paeff (author):::Contributor:::::::::::: (United States; Chicago; Follet & Pub. Co.)
Illustrated cover of children's book depicting Beethoven playing piano.